ETL processes specifications generation through goal-ontology approach - Ta'a, Azman (2011)
The common design-related problems for extract, transform, load (ETL) processes are far away from being resolved due to the variation and ambiguity of user requirements and the complexity of ETL operations.These were the fundamental issues of data conflicts in heterogeneous information sharing environments.Current approaches are based on existing software requirement methods that have limitations on reconciliation of the user semantics toward the modeling of the DW. This will prolong the process to generate the ETL processes specifications accordingly.The solution in this paper is focused on the requirement analysis method for designing the ETL processes. The method - RAMEPs (Requirement Analysis Method for ETL Processes) was developed to support the design of ETL processes by analyzing and producing the DW requirements in perspectives of organization, decision-makers, and developers.The ETL processes are modeled and designed by capturing DW schemas and data sources integration and transformation. The validation of RAMEPs emphasizes on the correctness of the goal-oriented and ontology requirement model, and was validated by using compliant tools that support both these approaches.The correctness of RAMEPs was evaluated in three real case studies of Student Affairs System, Gas Utility System, and Graduate Entrepreneur System.These case studies were used to illustrate how the RAMEPs method was implemented in generating the ETL processes specifications.